Comment on â€œRisk Factors Associated With Low Birth Weightâ€ - Khanal, V (Journal of Nepal Health Research Council, 2012)
In 2011 Oct issue, Journal of Nepal Health Research Council published an article â€œrisk factors associated with low birth weightâ€ by Yadav DK affiliated to School of Health and Allied Sciences, Pokhara University, Chaudhary U affiliated to Child Welfare Scheme, Kaski, and Shrestha N from CIST College, Kathmandu, Nepal. As a result, comments were sent to JNHRC, and are published below. Yadav DK, Chaudhary U, Shrestha N. Risk Factors Associated with Low Birth Weight. J Nepal Health Res Counc 2011 Oct;9(19):159-64. PMID: 22929846.